2012
DOI: 10.1007/s00066-012-0083-6
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative periclavicular radiotherapy in breast cancer patients with 1–3 positive axillary lymph nodes

Abstract: We could not demonstrate any difference in outcome in breast cancer patients with 1-3 positive axillary lymph node metastases with or without periclavicular lymph node irradiation. In addition, patients with PCLNI did not complain about higher rates of late toxicities. However, patients with ECS, which may predict for locoregional failure, may benefit from adjuvant periclavicular irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Yu et al (2013) reported supraclavicular radiation therapy (SCRT) was a significant predictor of locoregional recurrence-free survival (but not DMFS or OS) in patients with ≥2 risk factors. Biancosino et al (2012) reported RT to the supraclavicular and infraclavicular lymphatic drainage area in patients with positive ALN who underwent breastpreserving surgery failed to improve the focal control, disease-free survival, and OS. Macdonald et al (2009) compared RT at chest wall alone with RT at the chest wall and supra-and infraclavicular lymphatic drainage area in patients who underwent complete mastectomy due to T1-2N1 breast cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Yu et al (2013) reported supraclavicular radiation therapy (SCRT) was a significant predictor of locoregional recurrence-free survival (but not DMFS or OS) in patients with ≥2 risk factors. Biancosino et al (2012) reported RT to the supraclavicular and infraclavicular lymphatic drainage area in patients with positive ALN who underwent breastpreserving surgery failed to improve the focal control, disease-free survival, and OS. Macdonald et al (2009) compared RT at chest wall alone with RT at the chest wall and supra-and infraclavicular lymphatic drainage area in patients who underwent complete mastectomy due to T1-2N1 breast cancer.…”
Section: Discussionmentioning
confidence: 98%
“…The authors concluded that there was no benefit associated with the addition of supraclavicular irradiation for patients treated with a modern systemic therapy regimen. Similarly, Biancosino et al [25] compared clinical outcomes among pN1 breast cancer patients who underwent breast-conserving surgery and breast irradiation with or without periclavicular irradiation. The authors reported no statistical differences in terms of LRR-free survival, DFS, or OS.…”
Section: Discussionmentioning
confidence: 99%
“…Sharma et al [ 6 ] also found that the 10-year LRR of patients with stage T2 breast cancer was higher than that of patients with stage T1 cancer ( p =0.020). In addition, several reports demonstrated that patients with 2–3 positive nodes had a higher risk of supraclavicular fossa recurrence than those with 1 positive node, suggesting that supraclavicular fossa radiotherapy should be considered in the subset of patients with 2–3 positive nodes [ 28 29 ].…”
Section: Discussionmentioning
confidence: 99%